2017
DOI: 10.1016/j.heliyon.2017.e00480
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of MRI safety practices in Ghana

Abstract: ObjectiveThe aim of the present study was to assess current MRI safety practices among MRI facilities in Ghana, and their compliance with the 2013 American College of Radiology (ACR) guidance document on MR safe practices.Material and methodsA questionnaire developed from the 2013 ACR Guidance Document was used to collect information on magnetic field strengths, MR safety policy and compliance, patient screening, emergency preparedness, infection control, MRI safety accessories, equipment safety, signage and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…However, it was noted during a walk-through survey that there was a health and safety policy for the entire clinical imaging department. Similar MR safety non-compliance has also been noted in a Ghanaian study [24]. Cross et al [5] and Kanal et al [6] suggest that MRI facilities must have specific and updated MR safety policies and this was not found during the observations made in both hospitals.…”
Section: Base-line Risk Assessmentsupporting
confidence: 68%
“…However, it was noted during a walk-through survey that there was a health and safety policy for the entire clinical imaging department. Similar MR safety non-compliance has also been noted in a Ghanaian study [24]. Cross et al [5] and Kanal et al [6] suggest that MRI facilities must have specific and updated MR safety policies and this was not found during the observations made in both hospitals.…”
Section: Base-line Risk Assessmentsupporting
confidence: 68%
“…This could be disconcerting, thus reflecting the low level of MRI safety knowledge and awareness of the MRI safety issues. Piersson and Gorleku, 39 in their national MRI safety survey, found that about half of the surveyed centers had no MRI safety policy document in the workplace. Opoku et al 40 also found a lack of knowledge and training gap among MRI staff that might contribute to the absence of such cornerstone documents.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are much less than those found in Greece and Ghana studies. 39 , 45 Therefore, the training of staff involved in emergency response is essential to improve an organization’s ability to deal with any type of emergency to ensure that staff feels confident and competent in any emergency situation they may encounter during their clinical practice. 46 …”
Section: Discussionmentioning
confidence: 99%
“…It is essential for all MRI staff to realize safety aims, objectives, and targets for all safety issues in the MRI units. 9 It was also noted that when changes or upgrades, either in hardware or software, were brought about to the MR machine, safety policies were not updated. This was due to the perception that the scanner in hospital B was very recent and no upgrades had been due at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…This, however, in both hospitals is done by MRI vendors when conducting periodic maintenance. Although many MRI incidents occur as a result of improper screening or inappropriate access control, 9 it was noted that in both hospitals, there is restricted access to anyone entering the MRI suite. The responses of participants revealed that MR and non-MRI staff members are allowed to enter zone III or IV without undergoing safety screening, consequently putting them at risk of exposure to magnetic fields.…”
Section: Discussionmentioning
confidence: 99%